Implementation of Total Quality Management in Secondary Education: Challenges and Institutional Quality Transformation - Rima Fatmawati; Wieda Muqaffa; Fakhruddin Fakhruddin (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study investigates the implementation of Total Quality Management (TQM) in improving educational quality at SMA Negeri 4 Pekalongan by examining leadership commitment, stakeholder involvement, and continuous improvement practices. A qualitative case study design was employed involving 15 participants, including the principal, teachers, administrative staff, students, and parents. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed using the Miles and Huberman interactive model with triangulation to ensure trustworthiness. The findings indicate that TQM implementation remains in a transitional stage and has not yet been fully institutionalized as an organizational culture. Although school leadership demonstrates strong commitment through planning, supervision, and evaluation, follow-up actions remain limited and largely procedural. Stakeholder participation is still concentrated on operational activities, while continuous improvement is constrained by weak data utilization and fragmented evaluation systems. This study contributes empirical evidence on TQM implementation in Indonesian secondary schools and highlights the importance of participatory governance, evidence-based decision-making, and sustainable quality culture to strengthen institutional effectiveness.